2018
DOI: 10.1634/theoncologist.2018-0152
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of HER2 Amplification in Brain Metastases from Primary Gastrointestinal Malignancies

Abstract: Background In nongastric gastrointestinal (GI) cancers, HER2‐positive (HER2+) disease is not common. In breast cancer, HER2 status is associated with increased risk of brain metastases and response to HER2‐targeted therapy. The purpose of this project was to compare HER2 status in GI cancer brain metastases versus matched prior sites of disease in order to determine if HER2+ disease is more common intracranially. Materials and Methods We identified 28 patients with GI cancer who had craniotomy for brain metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Other studies also reported that the most common histological type accompanied by brain metastases was adenocarcinoma [ 6 , 12 ]. The mechanism behind the increased risk of brain metastases in esophageal adenocarcinoma may be related to the overexpression of HER2 [ 13 , 14 ]. However, some previous studies had conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also reported that the most common histological type accompanied by brain metastases was adenocarcinoma [ 6 , 12 ]. The mechanism behind the increased risk of brain metastases in esophageal adenocarcinoma may be related to the overexpression of HER2 [ 13 , 14 ]. However, some previous studies had conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…Aprile et al and Mitra et al reported cases of HER2/neu positivity in BM from CRC, while the original tumor sample was HER2/neu-negative. HER2/neu expression might also be associated with a potential negative prognostic value in BM (HER2/neu+: 4.6 months, HER2/neu–: 6.5 months) [ 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tan et al 15 recently pointed out that 20% of 40 patients with mCRC developing CNS metastases were characterized by ERBB2 amplification in the primary tumor. In another recent publication, 22 14 patients with mCRC undergoing craniotomy because of CNS metastasis were tested by IHC and FISH for ERBB2 amplification and 3 of them (21%) resulted positive with 100% concordance with primary tumor. These data, together with present findings from a selected population of HER2positive patients with mCRC, support the hypothesis that ERBB2 amplification, as also DNA damage response pathway defects, 23 is a mechanism that drives higher propensity to spread to CNS.…”
Section: Discussionmentioning
confidence: 99%